Severe acute malnutrition in children aged under 5 years can be successfully managed in a non‐emergency routine community healthcare setting in Ghana. Issue 4 (10th February 2017) - Akparibo, Robert; Harris, Janet; Blank, Lindsay; Campbell, Mike J.; Holdsworth, Michelle
Abstract: This study investigated the performance of community‐based management of severe acute malnutrition (CMAM) within routine healthcare services in Ghana. This was a retrospective cohort study of n = 488 children (6–59 months) who had received CMAM. Data for recovery, default, and mortality rates were obtained from enrolment cards in 56 outpatient centres in Upper East region, Ghana. Satisfactory rates of recovery of 71.8% were reported. Children who were enrolled with higher mid‐upper arm circumference (MUAC) ≥11.5 cm had seven times greater chance of recovery compared with children who were enrolled with lower MUAC <11.5 cm, OR = 7.35, 95% CI [2.56, 21.15], p < .001. Children who were diagnosed without malaria at baseline were 30 times, OR = 30.39, 95% CI [10.02, 92.13], p < .001, more likely to recover compared with those with malaria ( p < .001). The average weight gain was 4.7 g −1 ·kg −1 ·day −1, which was influenced by MUAC status at baseline, β = .78, 95% CI [0.46, 1.00], p < .001, presence of malaria, β = −1.25, 95% CI [−1.58, 0.92], p < .001, and length of stay, β = 0.13, 95% CI [0.08, 0.18], p < .001. The default rate (28.5%) was higher than international standards recommendations by Sphere. Mortality rate (1.6%) was lower than international standards. Our findings suggest that community‐based management of SAM can achieve similar success when delivered in routine non‐emergency settings. However, this success can be diluted by a high default rate, and the factors contributing to this need to be explored to improve programme effectiveness within communities.